Trends and biopsychosocial correlates of physical disabilities among older men and women in Taiwan: examination based on ADL, IADL, mobility, and frailty - Ching-Ju Chiu; Meng-Ling Li; Chieh-Ying Chou (BMC Geriatrics, 2022)
Abstract Background This study examines correlates of disabilities related to ADL, IADL, mobility, and frailty in men and women with a nationally representative sample of older adults living in the community. Methods A total of 10,898 noninstitutionalized Taiwanese nationals aged 65 years and older enrolled in the 2001 (N = 2,064), 2005 (N = 2,727), 2009 (N = 2,904), and 2013 (N = 3,203) National Health Interview Survey (NHIS) were analyzed. Results The prevalence of mobility disabilities and frailty in older adults in Taiwan decreased during the past decade ( $${χ }_{Mobility}^{2}= -5.4$$ χ Mobility 2 = - 5.4 , $${χ }_{Frailty}^{2}= -6.2$$ χ Frailty 2 = - 6.2 ). Exercise, social engagement, and tea and coffee intake were found to be associated with lower levels of all types of disabilities in both men and women. In addition, a diet based on carbohydrates, falls, depressive symptomatology, lung and metabolic diseases were risks for most of the disabilities under consideration. Gender-specific independent correlates included: being married (OR = 0.63, 95%CI: 0.40–0.98), eggs/beans/fish/meat consumption (OR = 0.35, 95% CI = 0.16–0.80); depressive symptoms, obesity and cataracts, which were associated with higher IADL (OR = 3.61, 1.63, and 1.18, respectively) and frailty limitations (OR = 10.89, 1.27, and 1.20, respectively) in women. Cognitive impairment was found to be an important correlate for ADL limitations in men (OR = 3.64, 95%CI: 2.38–5.57). Conclusions Exercise, social participation and diet (more tea and coffee intake and lower carbohydrates) were correlates for lower levels of disability. Some gender-specific correlates were also identified, including associations of disability with depressive symptoms, obesity, and cataracts that were more distinct in women, and lower levels of disability which were especially significant in men who were married, eat more eggs, beans, fish, and meat, and those free from cognitive impairment.